Part 8. (1st June 2015) - Davis, Christine; Lyall, Scott; Leslie, Esther; Bohme, Gernot; Latour, Bruno; Stengers, Isabelle
Entries: Phosporescence, Fog, Atmosphere, Air, Water, Pixels. Includes text by Christine Davis, Scott Lyall, Esther Leslie, Gernot Bohme, Bruno Latour, Isabelle Stengers. Artworks by Christine Davis, Ian Cheng, Fujiko Nakaya, Jean-Luc Moulene, John Sabraw, June Pak, Rafael Ochoa, Jack Goldstein. Also includes End Notes and Masthead for issue.